Anti-CTLA-and anti-PD-1 immune checkpoint inhibitor antibodies impair human sperm motility in-vitro - Ilaria Cosci; Luca De Toni; Paolo Del Fiore; Andrea Di Nisio; Andrea Di Nisio; Samuela Carraro; Claudia Maria Radu; Loris Bertazza; Simone Mocellin; Simone Mocellin; Jacopo Pigozzo; Giovanna Crivellaro; et al. (Frontiers in Pharmacology)
BackgroundImmune checkpoint inhibitors (ICIs), namely, anti-cytotoxic T lymphocyte-associated protein 4 (CTLA-4) monoclonal antibody Ipilimumab and anti- and programmed cell death 1 (PD-1) monoclonal antibodies Nivolumab, and Pembrolizumab, have improved the treatment outcomes for many other cancer types. However, their impact on fertility remains under-explored.MethodsThe possible direct effects of ICIs on human sperm was investigated. Spermatozoa from ten normozoospermic donors were exposed to Ipilimumab, Nivolumab, or Pembrolizumab at concentrations ranging from 1 to 100 ng/mL. Sperm motility was assessed through standard laboratory process. Cell viability and apoptosis markers were evaluated by flow-cytometry using fluorescent Annexin-V probe and Terminal Uridine Nick-End Label (TUNEL) assays. Protein-A-purified therapeutic antibodies (IgG) were also evaluated.ResultsSpermatozoa had high PD-1 (>99%) and negligible CTLA-4 expression. Exposure to ICIs, was associated with a concentration-dependent impairment of sperm motility, noticeable for Pembrolizumab and Ipilimumab since 10 ng/mL, and for Nivolumab since 100 ng/mL. However, no significant effect on cell apoptosis or viability was shown. Purified IgG from ICIs maintained the adverse effect on cell motility without affecting viability.ConclusionICIs, specifically Pembrolizumab, Nivolumab, and Ipilimumab, adversely affect human sperm motility in vitro. Further research is required to understand the underlying mechanisms and clinical implications.